Honesty and Intermediation: Corporate Cheating, Auditor Involvement and the Implications for Takeoff - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2012)
We examine honesty and credible auditing in firm-investor relations in a repeated game of imperfect information, embedded in a general equilibrium framework. Informed auditors enhance credibility over a range of audit fees – despite the auditor’s incentive to collude – provided the probability of detection is imperfectly correlated across clients. Auditing can enhance growth especially for a relatively egalitarian distribution of wealth. We show that audit fees must be neither too high nor too low to enhance client credibility, highlight the role of mandatory audit fee disclosure, interpret international differences in shareholding patterns and uncover a possible rationale for audit industry concentration.